EFFECTS OF LANGUAGE USE IN THE TRIAL OF THE PREMEDITATED MURDER CASE OF BRIGADIER JOSHUA - Khafid Roziki; Melinda Raswari Jambak; Chesa Andreana (LLDIKTI Wilayah X, 2024)
This study discusses the use of language in the context of criminal justice. The aims of this research are (1) to reveal the language used in the trial of the murder of Brigadier Joshua by the parties involved, such as witnesses, lawyers, judges, and defendants, and (2) to reveal the impact of the use of language in the trial of the murder of Brigadier Joshua on the outcome end of trial and justice in the criminal justice system. Data source from Kompas TV's YouTube channel. This research method is descriptive qualitative. Data collection techniques uses observation and note-taking techniques. Then, the data analysis technique uses the Miles and Huberman model, namely data reduction, data exposure, and conclusion. The result of this research is that the research found the language used in the trial by the related parties: (1) straightforward language, (2) accurate language, (3) effective language, and (4) relevant language. Then, the research also found 3 impacts of the use of language in the trial of the Brigadier Joshua murder case on the final outcome of the trial and justice in the criminal justice system, namely: (1) legal impact, (2) psychological impact, and (3) social impact.